Evaluation of thermotherapy on potato tubers to control tuber-borne nematodes, Meloidogyne spp. - Kurniawan, Wawan; Supramana, Supramana; Munif, Abdul; Giyanto, Giyanto (Kultivasi, 2025)
Root knot nematodes (Meloidogyne spp.) are significant plant-parasitic nematodes frequently transmitted through potato tubers and are a major factor contributing to the decline in both crop quality and yield. This study aims to evaluate the effectiveness of thermotherapy for eliminating Meloidogyne spp. from potato tubers and its impact on sprouting viability. Thermotherapy was conducted by immersing potato tubers and second-stage juveniles (J2) of Meloidogyne spp. in water at temperatures of 50 °C, 52.5 °C, 55 °C, and 60 °C for durations ranging from 5 to 75 minutes, depending on the treatment. Parameters observed included the mortality rate of Meloidogyne spp. J2 and the growth viability of potato seeds. The results showed that thermotherapy applied to second-stage juveniles (J2) of Meloidogyne spp. at 50 °C for 20 minutes resulted in complete (100%) nematode mortality. Similarly, the application of thermotherapy to potato tubers at 50 °C for 40 minutes did not significantly affect seed viability. During this treatment, the internal temperature of the tubers, measured at a depth of 1.5 cm, reached the target temperature of 50 °C at the 20-minute mark and was maintained until the 40th minute, ensuring an effective thermal exposure. These results indicate that thermotherapy at 50 °C for 40 minutes represents a safe and effective method for the elimination of Meloidogyne spp. in potato tubers. This approach offers a practical and promising strategy to enhance seed health and minimize the risk of nematode dissemination in potato cultivation systems.